Reverse Logistics in Food Industries: A Case Study in Malaysia - Irdiana Noor Ngadiman; Mehdi Moeinaddini; Jamilahtun Binti Ghazali; Nuur Fathin Binti Roslan (International Journal of Supply Chain Management, 2016)
This paper is demonstrated the reverse logistics in the food and beverage industries in Malaysia. Reverse logistics defined as the return, exchange, refurbishment, remarketing and disposition of products. The customer returns the products because of several reasons such as end of life, expired, product damage, products recall, poor quality and non halal products. The successful implementing reverse logistics industries can be a benchmark to the other food and beverage industries. This study is based on quantitative data collected by distributing the questionnaire to hypermarkets and one beverage company as a benchmark. The descriptive analysis shows that the significant factors those make reverse logistics success are based on the framework dimensions on: Why- Returning (the return reasons by the end user or customer), Why- Receiving (driving forces for implementing reverse logistics activities), What (the type of products and the products characteristics), How (the recovery processes and recovery option), and Who (the actors involved and their roles). The aims of this study thereby is to investigate the challenges that faced with application of reverse logistics at the organization are influenced by the internal and external barriers. The contribution of the study is to highlight the present scenario of reverse logistics practices to academicians and industries. Keywords: Reverse Logistics, Food and Beverage Industries, Challenges, Returning